Correction: Advancing automatic text summarization: Unleashing enhanced binary multi-objective grey wolf optimization with mutation - Sheikh, Muhammad Ayyaz; Bashir, Maryam; Suddle, Mehtab Kiran (PloS one, 2024)
[This corrects the article DOI: 10.1371/journal.pone.0304057.].